(untitled) (Research, Society and Development, 2022)
Objective: To characterize the clinical-epidemiological profile – based on parameters of functional respiratory capacity, dyspnea, gravity and sociodemographic characteristics – two patients with COPD monitored at a pneumology reference center in Alagoas. Methodology: This is an observational and cross-sectional study, based on the application of a standardized questionnaire - Modified British Medical Research Council (mMRc), assessment of medical records and spirometry of patients previously diagnosed with COPD in the Pulmonology sector of the Hospital Universitário Professor Alberto Antunes (HUPAA). Results: A total of 46 patients were analyzed, obtaining a profile of female elderly (63%) who had or have smoking habits (78.3%) and other comorbidities, predominantly of cardiovascular origin. To assess the Global Initiative for Chronic Obstructive Lung Disease (GOLD) scale of patients, the mMRC was applied together with the number of annual exacerbations of the disease and classified as A (52%), B (19.5%), C (2.1%) or D (26%). As for the severity of the disease, the Forced Expiratory Value in the First Second (FEV1) was less than 50% of the predicted value in more than 70% of the patients, therefore, considered severe or very severe. Conclusion: The epidemiological profile of patients is consistent with world studies, with the exception of the prevalence of women to the detriment of men. Patients have a relatively average quality of life based on the mMRC. On the other hand, in terms of disease severity, patients with severe and very severe COPD stand out.